'Stepping on the teacher's toes': student teachers' experience of a one-year postgraduate teacher training programme. Issue 5 (20th October 2022) - Backhouse, Anita
ABSTRACT: Student teachers engaging in periods of training in the classroom, supported by experienced mentors, is an accepted model for teacher training. This qualitative study adopted a descriptive phenomenological approach to establish the lived experience of a group of postgraduate primary student teachers across their teacher training year. A community of practice theoretical lens was applied and findings suggested that in some cases student teachers can be regarded as legitimate peripheral participants (LPP) in a primary school context and learning gains made. However, learning and successful outcomes were still shown to take place even when the student teachers might not be regarded as LLPs. There are therefore limitations to the community of practice model. Attention paid to student teachers' individual circumstances might better contribute to their self-efficacy and subsequent motivation to enter the teaching profession. There are implications for mentor training and further research.